Islamic Education Policy in Yogyakarta 2020-2025: A Systematic Review of Its Implementation and Impact - Ardhitya Furqon Wicaksono; Sri Wahyu Budoyo Kusumo; Judi Antono; Arraywed Yudita Wibowo; Katty Febriliani Rahayu (South Sulawesi Education Development, 2025)
Between 2020 and 2025, Islamic education policy in the Special Region of Yogyakarta has experienced a significant transformation marked by the adoption of the Independent Curriculum (Kurikulum Merdeka), the digitalization of teaching and learning, and the institutionalization of religious moderation programs. This study aims to evaluate the implementation of these policies and measure their direct impact on the quality of education in madrasahs and other Islamic educational institutions. Using a Systematic Literature Review (SLR) combined with an evaluative framework, 32 peer-reviewed articles from reputable databases (Garuda, Google Scholar, SINTA) were analyzed based on topic relevance, source credibility, and publication year. The analysis shows that 68% of madrasahs have integrated digital learning platforms, 54% have fully adopted the Independent Curriculum, and 72% have implemented structured tolerance-strengthening initiatives. Despite these advancements, persistent challenges remain, limited financial resources for private madrasahs hinder infrastructure upgrades, inadequate teacher training restricts curriculum effectiveness, and weak intergovernmental coordination reduces policy oversight efficiency. The findings underline the importance of harmonizing national education directives with local socio-cultural contexts, ensuring policies are both adaptive and participatory. The study concludes that the long-term success of Islamic education policy in Yogyakarta is contingent upon improving implementation quality at the institutional level, strengthening human resource readiness, and sustaining infrastructure support. Strategic recommendations include reformulating policies to address local needs and investing in ongoing professional development for teachers. These measures are projected to enhance educational quality, institutional resilience, and the long-term sustainability of policy outcomes in the region.